Analyse comparative de pratiques d’animation d’une discussion à visée démocratique et philosophique vues sous l’angle de la temporalité - Christine Pierrisnard (Éducation et Socialisation)
This study focuses on how the tool « philosophically and democratilly oriented discussion » (RPRC) is transformed by its users into instrument over situations. The comparative analysis of practices rather a novice facilitator and an expert facilitator reveals three crucial elements of temporal representation of the situation RPRC. A wide time span, anchored in the long time required for the decline of thought ; the kairos, steeped in immediacy and urgency to seize the opportunity and spirality, inscribed in a time of repetition and variation favorable to deepening . These three experiential knowledge associated, detailed in this article and stated in terms of constituent operational invariants of an expert animation RPRC scheme, appear to be critical in the sense that they rely to a large extent the expertise of a discussion leader .